Pengaruh Emotional Intelegence (EI) dan Self Efficacy terhadap Employee Retention: Studi Kasus Karyawan di Koperasi Simpan Pinjam di Kabupaten Lamongan - Ahmad Maulana Bin Khoiri; Moh. Heru Budi Santoso (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2026)
This study aims to analyze the influence of emotional intelligence and self-efficacy on employee retention among employees at savings and loan cooperatives in Lamongan Regency. This research is motivated by the importance of retaining employees as organizational assets in facing increasingly complex business environments and competition. The research approach used is quantitative, grounded in Social Exchange Theory (SET), which explains that employee retention is formed through positive reciprocal relationships between employees and the organization. The study population was all employees at savings and loan cooperatives in Lamongan Regency, while the sample size was 93 respondents selected using a specific sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression. The results of the study show that emotional intelligence has a positive and significant effect on employee retention, indicating that employees' ability to recognize, manage, and utilize emotions effectively can increase their desire to remain with the organization. Meanwhile, self-efficacy did not have a positive effect on employee retention, indicating that an individual's belief in their abilities is not necessarily the primary factor determining an employee's decision to remain with the organization. However, emotional intelligence and self-efficacy simultaneously had a positive and significant effect on employee retention, so that the two variables together can explain variation in employee retention.